Cryptgrapy Algorithm Variably Modified Permutation Compotition (VMPC) on Image Security - Eva Sasmita; Yani Maulita; Juliana Naftali Sitompul (CV. AFDIFAL MAJU BERKAH, 2022)
The development of technology as it is today allows everyone to exchange information without any limitations of time and distance. The possibility that there will be a data leak during the information exchange process is carried out. Therefore, in sending data, especially images, aspects of security, confidentiality and efficiency of data storage are very necessary. If this important information falls into the wrong hands, it will cause unwanted things, for example image manipulation in a negative form and can harm the owner of the image. One of the methods used to maintain the security of the data is cryptography using one of the techniques, namely Vmpc. The strength of this algorithm lies in the difficulty of calculating discrete algorithms on prime integers in which multiplication operations are performed. In this study, the author encodes the image encryption with the Vmpc Algorithm to decrypt the key from Vmpc. System implementation using Visual Basic Net 2010 programming language.The results of the implementation with the initial encrypted image having a time of 4282.85 Milliseconds with randomized image results while the encrypted image will be re-decrypted which has a time of 20442.84 Milliseconds with the image results returning to the beginning.